Development of Numerical Thought. A Strategy: Animaplano (2017)
Promoting mathematics meaningful learning has been a constant concern of teachers, who persistently seek different pedagogical strategies so that students, in a creative and playful way, develop the necessary skills. Numerical thought, as a mathematical ability to understand numbers, their symbols, their meanings and their relations, enables the realization of cognitive activities (numerical configuration, analysis of phenomena, questions and problems that employ numerical elements), that structure complex processes of thought which will serve the subject to understand other mathematical aspects. This is how the animaplano is a methodological proposal designed by the research group “Didactics and Mathematics”, as a tool to develop numerical thought in a fun way. One of the conclusions is the real need to develop competences in numerical thought, which will allow students to have a better development in their daily lives and will be the basis on which general mathematical knowledge is structured. This review article is a product of the research developed between 2016 and 2017 with students of fourth grade of School in Institución Educativa Simón Bolívar of Soracá (Boyacá, Colombia). The purpose of this research was to take the animaplano as a tool that would enable interdisciplinary work, from learning mathematics (understanding reader, numerical thought, aesthetic skill).